VALIDITAS DAN RELIABILITAS ANGKET KEDISIPLINAN SISW - Suciainsani, Okky; Eti Rohaeti, Euis; Yuiliani, Wiwin (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2024)
The purpose of the research conducted is to find out the level of validity and reliability of the student discipline that has been prepared. Where in this study used research and development methods to help in the manufacture of questionnaires, as well as test the effectiveness of the questionnaire. The subjects in this study were class IX students in SMP Karya Pembangunan which amounted to 15 students. From the results of the validity test in the study conducted it was produced that the packages arranged were in a valid category, where in the reliability test results were produced a score of 0.808 which of the results were compiled including the reliable category. So from the results of research conducted angket compiled can be used in measuring the scale of student discipline.